TINJAUAN YURIDIS PELAKSANAAN PERJANJIAN JUAL BELI TENAGA LISTRIK ANTARA KONSUMEN DENGAN PT. PLN (PERSERO) DI WILAYAH KOTA KUPANG - Maria Gabriella Kuma Namang; Orpa Juliana Nubatonis; Husni Kusuma Dinata (Petitum Law Journal, 2026)
This study explores the implementation of electricity sales contracts between PT. PLN (Persero) and customers in Kupang City from a legal perspective, with an emphasis on the types of default and how to resolve conflicts. Using empirical methods including interviews with PLN employees and customers and document analysis (SPJBTL, Electricity Law, Civil Code), the results obtained indicate that the contracts used are standard and unilateral, resulting in an imbalance between rights and obligations. Customers often commit defaults such as late payments, bill deletions, and energy theft (there were 25 cases), which were caused by economic factors and disputes over assets. PT. PLN addresses this problem through a tiered Electricity Usage Control mechanism: giving warnings, imposing fines, disconnecting connections, and meetings to discuss sanction relief. Although the contract is considered valid according to Article 1320 of the Civil Code, the dominance of clauses by PLN can cause injustice to consumers, so strengthening the negotiation aspect in the contract is very necessary.